The Investigation of University Students Knowledge and Behaviors About Rational Drug Use - Altun, Umutcan; Korkmaz Öner, Fatma Semanur; Türk, Amine Başak (Turkey Health Literacy Journal, 2022)
The Problem of The Research: Adherence to treatment decreases, drug interactions, and the frequency of adverse reactions increase due to the principles of rational drug use are not followed by the public.The Aim of The Study: This study aimed to evaluate the knowledge and behaviors about the rational drug use of Medicine, Pharmacy, Health Management, and Nursing students who receive health education.Method: The snowball sampling method was used in this descriptive study. A total of 749 students from the departments of Medicine, Pharmacy, Nursing, and Health Management who agreed to participate in the study were asked to answer 36 questions online. Statistical Package for Social Sciences (SPSS), version 22.0 for Windows (SPSS Inc. Chicago, USA) computer package program was used for statistical analysis of the data. In the descriptive statistics section, categorical variables are given as numbers and percentages, and continuous variables are presented as mean ± standard deviation and median (smallest – largest value). Conformity of continuous variables to normal distribution was evaluated using visual (histogram and probability graphs) and analytical methods (KolmogorovSmirnov/Shapiro-Wilk tests). Chi square test was used in the comparison analyzes of categorical variables. In this study, the statisticalsignificance level was accepted as p
Keywords: Rational Drug Use; University Students; Health Literacy